The Effect of Student Team Achievement Division (STAD) on Student Learning Outcomes of SMP Negeri 1 Tinondo - Tri Maniarta Sari; Ramad Arya Fitra; Rismayanti Rismayanti (Journal of Biological Science and Education, 2022)
The learning model is very influential on the success of learning. the right learning model can affect learning outcomes in the classroom. This study aims to determine the effect of the model Student Team Achievement Division (STAD) on the Learning Outcomes of Class VIII Students of SMP Negeri 1 Tinondo. The type of research used in this study is a Quasy Experiment type of research. The total population in this study were 48 students of class VIII at SMP Negeri 1 Tinondo. The sample used in this study consisted of two classes, namely: the experimental class (Class VIII A totaling 24 students), and the control class (Class VIII B totaling 24 students). With the research design Control Group Pretest-Posttest Design. The instrument used to measure learning achievement tests is an essay test in the form of a pretest and posttest. The instrument used to measure learning achievement tests is an essay test in the form of a pretest and posttest. data analysis technique using independent sample t-test. The results showed that, After the pretest and posttest were carried out in the experimental class using the STAD learning method, the independent t-test value of the N-gain sample t-test was obtained with the t-count value t-table. Based on the table above, it is known that the t count is 7,926 with a significance of 0.000. The t-table obtained from df = 46 at a significant level of 5% is 2.018. So t-count t-table. So there are differences in student learning outcomes scores in different ways significantly between the experimental class and the control class. Based on the results of the study, it can be concluded that the model Student Team Achievement Division (STAD) learning can affect the learning outcomes of science at SMP Negeri 1 Tinondo. Keywords: STAD learning model, Student learning outcomes.